Prevalence of arterial hypertension and its risk factors in young adults of Paraguay - Lugo, Gladys B. (2019)
Early detection of arterial hypertension is critical for preventing the occurrence of cardiovascular diseases. A cross-sectional, observational, descriptive study was performed in order to determine the prevalence of arterial hypertension and cardiovascular risk factors among young university students in Paraguay. WHO hypertension parameters were used to classify the hypertension status. The research demonstrated that 18.6% of the students were classified in the prehypertension and 2.2% of the population had already a hypertension stage I status. 25.8% of the students had exceed the normal body mass index and 67.4% had a family history of hypertension. The values of blood pressure and family history were very unusual among youth population and in relation to similar population around the world.